Importancia de la preparación física de los árbitros de fútbol y sus incidencias en el desempeño arbitral (Revista Electrónica REDINE, 2024)
For decades, football has been considered the most popular sport in the world, coupled with the fact that it is a sporting discipline that generates many positive emotions, feelings of joy, satisfaction and happiness, in players, specialists, practitioners, fans and even in the common citizen. It is true that it has also led to moments of disagreement and adversity, however, for the most part it has maintained attention and passion for human beings. Added to these assertions, this collective sport maintains a demanding rhythm in the practitioners and in the refereeing body that is responsible for enforcing the legal rules of the match. In this sense, the present investigative study seeks to know the importance of the physical preparation of soccer judges and its impact on referee performance. For this reason, a bibliographic review will be carried out framed in some previous studies, referential theories and proposals linked to this type of topic mentioned above. The method was based on a documentary investigation that allowed information to be collected through the use of books, files and records in the internet search engine known as Google. In turn, a diagnosis was carried out by applying the interval test for soccer referees to the subjects (8) belonging to the sample to be studied. The results achieved allowed us to detect that, if there are problems with the physical preparation of the referees, injuries suffered, or they are unaware of benevolent exercises for their physical condition, among others. Furthermore, the interval test allowed us to know that these judges have an equivalent distance travel. Based on these results, recommendations were made based on propositions to minimize these problems described above and provide a theoretical contribution that contributes to the comprehensive training of the field soccer referee.
Keywords: Preparación física e importancia; fútbol; árbitros de fútbol; desempeño arbitral; Physical preparation and importance; soccer; soccer referees; referee performance